Wear and Friction of AA5052-Al3Zr in Situ Composites Synthesized by Direct Melt Reaction - Gautam G.; Mohan A. (My University, 2025)
Particulate aluminum matrix composites (PAMCs) with different volume percent of Al3Zr particles have been developed by direct melt reaction (DMR). Wear and friction have been studied in detail for all compositions under dry sliding conditions. Results indicate that the wear rate, normalized wear rate, and wear coefficient of PAMCs decrease continuously with increase in volume percent of Al3Zr particles, however, with applied load and sliding distance, wear continuously increases. Wear rate and wear coefficient with sliding velocity initially decrease for all compositions, attains minima, and then increase sharply. However, coefficient of friction shows increasing trend with composition and sliding velocity but with load it shows a decreasing trend and with distance slid it fluctuates within a value of ±0.025. At low load and sliding velocity three-dimensional (3D)-profilometer, scanning electron microscope (SEM), and debris studies show low Ra values and mild wear dominated by oxidative nature, whereas at high loads and sliding velocities high Ra values and wear nature change to severe wear with mixed mode (oxidative-metallic) and surface with deep grooves is observed. Further, it is also important to note from morphological studies that refinement of matrix phase takes place with in situ formation of Al3Zr particles, which helps to improve hardness and tensile properties finally contributing to low wear rate. © 2016 by ASME.